Vision Correction and Eye Surgery - Lo Giudice, Giuseppe (IntechOpen, 2022)
This book focuses on the current approaches in the medical and surgical treatment of the most diffuse and important ocular diseases. It reports the latest developments in surgery (anterior segment surgery, posterior pole surgery, etc.) for various types of ocular disease, including glaucoma, corneal diseases, and vitreoretinal disease. the latest developments in the surgical field of ocular disease from the anterior segment to the posterior pole going through the main ocular disease (cataract surgery in normal and/or complicated conditions, glaucoma, corneal diseases, and vitreoretinal disease), with the latest developments in the treatment of ocular disease that enable improved surgical outcomes and fewer complications.